2019
DOI: 10.3390/ijms20071754
|View full text |Cite
|
Sign up to set email alerts
|

The miRNA-Mediated Post-Transcriptional Regulation of Maize in Response to High Temperature

Abstract: High temperature (HT) has recently become one of the most important abiotic stresses restricting crop production worldwide. MicroRNAs (miRNAs) are important regulators in plant development and stress responses. However, knowledge of miRNAs of maize in response to HT is limited. In this study, we simultaneously adopted miRNA sequencing and transcriptome profiling to analyze the differential expression of miRNAs and mRNAs in maize during exposure to HT stress. Our analysis revealed 61 known miRNAs belonging to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 73 publications
4
19
0
Order By: Relevance
“…Besides miR156, heat stress affects other miRNAs and their target genes involved in protein folding, antioxidant response, photosynthesis protection, reproductive tissue protection, and flowering time regulation [ 80 , 111 ]. In maize, 61 known miRNAs belonging to 26 miRNA families and 42 novel miRNAs showed significant differential expression in the response to heat stress, with the majority being downregulated [ 81 , 112 ]. The reduction in miRNA levels leads to the upregulation of their targets, such as in the case of miR172-AP2.…”
Section: Enhancement Of Alternative Rna Splicing As a Heat Stress mentioning
confidence: 99%
See 1 more Smart Citation
“…Besides miR156, heat stress affects other miRNAs and their target genes involved in protein folding, antioxidant response, photosynthesis protection, reproductive tissue protection, and flowering time regulation [ 80 , 111 ]. In maize, 61 known miRNAs belonging to 26 miRNA families and 42 novel miRNAs showed significant differential expression in the response to heat stress, with the majority being downregulated [ 81 , 112 ]. The reduction in miRNA levels leads to the upregulation of their targets, such as in the case of miR172-AP2.…”
Section: Enhancement Of Alternative Rna Splicing As a Heat Stress mentioning
confidence: 99%
“…[ Identification of the miRNA in Arabidopsis and maize involved in post-transcriptional regulation of the response to heat stress [80,81] Unlike mammalian cells, most plant HSFs are themselves regulated by heat shock; some are upregulated, while others are downregulated. In Arabidopsis, HSFAs constitute a transcriptional cascade in which HSFs activate each other in response to environmental stress (Figure 3a and Table 1).…”
Section: Arabidopsis Maizementioning
confidence: 99%
“…Salinity stress [108] ghr-miR399 and ghr-156e Salt stress [94] miR319 Abiotic stress signaling [109] ghr-miR5272a Immune response [110] multiple miRNAs Salt stress [111] multiple miRNAs High temperature [112] multiple miRNAs Low and high temperature stress [113] miR156a/d/e, miR167a, miR169, miR397a/b, miR399a, miR535a/b, miR827b, Salt stress [114] Cowpea (Vigna unguiculata) multiple miRNAs Drought stress [115] Date Palm (Phoenix dactylifera) multiple miRNAs Salinity stress [116] Flax ( Linum usitatissimum) miR319, miR390, and miR393 Aluminum stress [117] Foxtail Millet (Setaria italica) multiple miRNAs Drought stress [118] multiple miRNAs Dehydration stress [119] Java waterdropwort (Oenanthe javanica) multiple miRNAs Various abiotic stress [120] Maize (Zea mays) multiple miRNAs Chilling stress [121] multiple miRNAs Heat stress [122] multiple miRNAs Nitrogen stress [123] multiple miRNAs Drought stress [82] multiple miRNAs Cadmium stress [124] multiple miRNAs Phosphate deficiency [125] multiple miRNAs Water logging [126] multiple miRNAs Nitrogen deficiency [127] multiple miRNAs Short term water logging [128] miR160, miR164, miR167, miR168, miR169, miR172, miR169, miR395, miR397, miR398, miR399, miR408, miR528, miR827…”
Section: Micrornas Stress Responses Referencementioning
confidence: 99%
“…Rising temperature is a global issue because of its impact on crop growth and yield (Wang et al, 2020a). Maize is more sensitive to heat stress (one of the most important abiotic stresses) than wheat and rice (Zhao et al, 2017;Zhang et al, 2019). Simulation result indicated that a 10% reduction in maize yield was shown for each 1 °C increase in global temperature (Zhang and Zhao, 2017;Dong et al, 2021).…”
Section: Introductionmentioning
confidence: 99%